1995
DOI: 10.1007/bf02064967
|View full text |Cite
|
Sign up to set email alerts
|

Newly synthesized histamine accelerates ornithine decarboxylase activity in rat intestinal mucosa after ischemia-reperfusion

Abstract: We previously demonstrated that both histamine synthesis (histidine decarboxylase activity) and polyamine synthesis (ornithine decarboxylase activity) increased in the rat intestinal mucosa after ischemia-reperfusion, whereas the relationship between these two factors remains unclear. To elucidate this relationship, we performed the present study. The superior mesenteric artery was occluded for 15 min followed by reperfusion. After ischemia-reperfusion, histidine decarboxylase activity and ornithine decarboxyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although reactive oxidative metabolites may contribute to the killing of H. pylori microorganisms, they may also injure the surrounding tissue (1). The role of HDC activation and histamine generation in the response to oxidant stress of the gastrointestinal tract remains unclear, although several studies have suggested that histamine synthesized by HDC may facilitate healing of the gut mucosa (23)(24)(25) and inhibit the further generation of ROMs by neutrophils (44,45). In addition, a role in acid secretion has been suggested by recent studies showing that H 2 O 2 at low concentrations is capable of stimulating acid secretion by sevenfold in isolated gastric mucosa (46).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Although reactive oxidative metabolites may contribute to the killing of H. pylori microorganisms, they may also injure the surrounding tissue (1). The role of HDC activation and histamine generation in the response to oxidant stress of the gastrointestinal tract remains unclear, although several studies have suggested that histamine synthesized by HDC may facilitate healing of the gut mucosa (23)(24)(25) and inhibit the further generation of ROMs by neutrophils (44,45). In addition, a role in acid secretion has been suggested by recent studies showing that H 2 O 2 at low concentrations is capable of stimulating acid secretion by sevenfold in isolated gastric mucosa (46).…”
Section: Discussionmentioning
confidence: 97%
“…Several previous observations have suggested that the HDC gene may be activated in the stomach under conditions of oxidative stress. For example, HDC activity has been shown to be increased during ischemia-reperfusion injury to the gastrointestinal tract (23)(24)(25). Experiments from our laboratory have shown that the HDC promoter is transcriptionally regulated by gastrin and the phorbol ester (phorbol 12-myristate 13-acetate, PMA) through a protein kinase C (PKC)-and MAP kinase-dependent pathway, acting on a 23-nucleotide cis-acting element, the gastrin response element (GAS-RE) (20,26,27).…”
mentioning
confidence: 99%
“…twice . daily for two consecutive days , in order to suppress endogenous histamine production from digestive ente-Ž rochromaffin-like cells Andersson et al, 1992;Fujimoto . et al, 1995 . The effects of CCK-8S were also examined Ž .…”
Section: Methodsmentioning
confidence: 99%
“…since: a pretreatment with a-fluoromethylhistidine, at doses that greatly decreased histidine decarboxylase activity and histamine concentration in digestive tissues Ž . Andersson et al, 1992;Fujimoto et al, 1995 , or with cimetidine did not interfere with CCK-8S-or gastrin-I-in-Ž . duced peptic hypersecretion; and b exogenous histamine Ž .…”
mentioning
confidence: 88%